HARNESSING SOCIAL MEDIA TO BOOST CONSUMER AWARENESS OF HALAL PRODUCTS IN - Yanti, Vanda Sekar (Journal of Halal Research, Policy, and Industry, 2024)
This research investigates the role of social media in enhancing consumer awareness of halal products in Indonesia. As the halal market continues to grow, effective strategies for boosting consumer knowledge and trust are essential. The study employs a quantitative approach. The findings reveal significant relationships between social media usage frequency, content quality, influencer marketing, and advertising on consumer awareness, trust, and attitudes toward halal products. Specifically, it was found that higher engagement on social media platforms correlates with increased awareness and trust in halal products, ultimately influencing purchase intentions. The research emphasizes the importance of influencer marketing and high-quality content in shaping consumer perceptions and recommends that brands leverage these elements to effectively reach and educate their target audience. The implications of this study contribute to the understanding of digital marketing strategies within the halal industry, providing insights for businesses seeking to enhance their presence in this competitive market.